Jacob of Sarug's Homily on Jephthah's daughter - Jacobus, Sarugensis 451-521 (Texts from Christian late antiquity, 2010)
Introduction -- Outline -- Jacob's exegesis of judges -- Text and translation -- Opening invocation -- The history of sacrifice -- Jephthah and the war with the ammonites -- Jephthah's vow -- The battle -- Jephthah's victory -- The bride of blood -- Jephthah's realization -- Justice speaks -- Jephthah's inner battle -- Jephthah's inner victory -- The daughter responds -- The daughter's offering -- Death trembles at her courage -- Jephthah's test renewed -- The daughter's lamentation -- The lamentation completed -- The poet's task -- Jephthah's sacrifice